The Readiness of Future Specialists of Preschool Education to Creative Self-Realization in Professional Activity - Ivanivna Lutsan, Nadia (2020)
The article is devoted to the issue of future specialists of preschool education training to creative self-realization in professional activity. The authors of the article reveal the pedagogical diagnostics of readiness to creative self-realization in professional activity of higher educational institutions’ students. The purpose of the study is to reveal the results of pedagogical diagnostics of future specialists of preschool education readiness to creative self-realization in professional activity. A diagnostic methodology and criteria of future specialists of preschool education to creative self-realization in professional activity readiness has developed. The criteria of future specialists of preschool education to creative self-realization in professional activity readiness are: motivational and valuable, creative activity, assessment and reflective. Each criterion includes a group of quality indicators. The methodological tools was developed, which was used for pedagogical diagnostics of this professional quality forming in future specialists of preschool education. The experimental study helped to identify the characteristics of qualitative measurements for primary, reproductive and creative levels of readiness of future preschool teachers’ professional training. We see the prospect of further research in the development of methodology of future specialists of preschool education preparing to creative self-realization in professional activity.